Hubungan Pola Asuh Ibu Dalam Pemberian Makan Ibu Dengan Kejadian Stunting Pada Balita Di Desa Jago, Aikmual - Yulandasari, Vera; Hardiansah, Yayan; Husen, Muhammad Sadam; Wiksuarini, Erwin; Mastuti, Amalia; Fanani, Akhmad (Yayasan Jompa Research and Development, 2025)
Stunting in toddlers is a major nutritional problem in Indonesia. This study aims to determine the relationship between maternal parenting patterns in feeding and stunting in toddlers aged 2–5 years in Jago Village. The research design was a correlation with a cross-sectional approach. The population was 109 respondents with a sample of 52 people using a purposive sampling technique. The instruments were questionnaires and height measuring tapes. The results of the Spearman Rank test showed that there was no significant relationship between maternal parenting patterns in feeding and stunting (p = 0.761). Conclusion: maternal parenting patterns in feeding are not significantly related to stunting. Keywords: Feeding, Maternal Parenting Patterns, Stunting